2018
DOI: 10.1136/bmjopen-2017-019312
|View full text |Cite
|
Sign up to set email alerts
|

Interagency collaboration models for people with mental ill health in contact with the police: a systematic scoping review

Abstract: ObjectiveTo identify existing evidence on interagency collaboration between law enforcement, emergency services, statutory services and third sector agencies regarding people with mental ill health.DesignSystematic scoping review. Scoping reviews map particular research areas to identify research gaps.Data sources and eligibilityASSIA, CENTRAL, the Cochrane Library databases, Criminal Justice Abstracts, ERIC, Embase, MEDLINE, PsycINFO, PROSPERO and Social Care Online and Social Sciences Citation Index were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 109 publications
0
42
0
Order By: Relevance
“…Firstly, the review only identified two outcomes studies, evaluating prearrest diversion in four independent sites. With the routine implementation of prearrest diversion in many police districts in many countries, this is surprisingly few (Parker et al, ). Although the search generated 60 potentially eligible studies, almost half were excluded on population, intervention, or study type (27).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the review only identified two outcomes studies, evaluating prearrest diversion in four independent sites. With the routine implementation of prearrest diversion in many police districts in many countries, this is surprisingly few (Parker et al, ). Although the search generated 60 potentially eligible studies, almost half were excluded on population, intervention, or study type (27).…”
Section: Discussionmentioning
confidence: 99%
“…A major perceived challenge to CMHCP implementation has been the lack of an evaluation plan. While there has been an increase of the co‐responder model in the United States, Canada, UK, and Australia, there remains a lack of rigorous research on the effectiveness of the model, particularly with regard to health outcomes (Parker et al ; Puntis et al ). CMHCP activities are logged by police and mental health team members into the respective data systems of health and police services, neither of which accurately reflect the total outputs of the CMHCP, particularly non‐crisis‐related activities, thereby hampering any quality improvement efforts.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…A recent scoping review of interagency collaboration models between the police and other agencies for people with apparent mental ill health identified a range of possible models. 14 These included:…”
Section: Implications For Researchmentioning
confidence: 99%
“…31 This resulted in five reviews being included in the synthesis. 11,12,14,15,39,40 There were six articles published for the five reviews as Kane et al 11 also published their review protocol. The remaining 25 review articles were excluded from the synthesis as their methods were deemed less robust (according to DARE criteria) or were not reported.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation